Carbon quantum dots decorated leaf-like CuO nanosheets and their improved dispersion for an excellent UV-shielding properties in polymer films1. Issue 88 (25th September 2015) - Periyayya, Uthirakumar; S, Muthulingam; Khan, Rizwan; Dao, Van-Dung; Tran, Van-Huong; Lee, In-Hwan
<x xml:space="preserve">Abstract</x> Carbon quantum dot decorated leaf-like CuO nanosheets were prepared by a simple method and successfully dispersed in the polymer film to improve UV-shielding properties.